Correlation Between Hypertension and Hyponatremia in Hospitalized Coronavirus Disease 2019 Patients: A Single-Center Experience - Ayu Pramitha Wulandari; Dhani Tri Wahyu Nugroho (Universitas Brawijaya, 2021)
Background: Hypertension has been presumed to be associated with the severity of coronavirus disease (COVID-19) related to angiotensin-converting enzyme 2 (ACE2). Besides, hyponatremia is the most common electrolyte disorder in COVID-19 patients and has been reported to be associated with increased mortality.Objective: This study aimed to evaluate the association between hypertension and hyponatremia in COVID-19 patients who were admitted to Wahidin Sudirohusodo General Hospital Mojokerto.Method: In this study, we cross-sectionally investigated COVID-19 patients who were admitted to Wahidin Sudirohusodo General Hospital Mojokerto between December 2020 and January 2021. According to medical records, we evaluated COVID-19 patients who have hypertension as comorbidities and hyponatremia from laboratory results. Result: There were 98 COVID-19 patients enrolled in this study. The prevalence was 51 % men and 49 % women. The mean number of patients age was 55.6 + 12.4 years. The prevalence of hypertension among patients was 55.1%. The mean number of sodium level was 131.50 + 11.29 mmol/L. There was a strong correlation between blood pressure and sodium balance disorders (p<0,002). Hypertension was associated with a nearly 5.5-fold increased risk of hyponatremia in COVID-19 patients (OR 5.06; 95% CI; 1.66-15.4; p<0,05).Conclusion: Hypertension comorbidity was associated with a higher risk of hyponatremia in COVID-19 patients.Keywords: Hypertension, Hyponatremia, COVID-19